Aspects of the regulation of inflorescence initiation in white clover (Trifolium repens L.) : a thesis ... for the degree of Master of Science in Botany at Massey University - Havell, David Charles (Massey University, 1982)
Thomas (1962), found that after a pretreatment of warm short days, one genotype of 'Grasslands Huia' white clover, clone C, flowered in long days. Another 'Grasslands Huia' genotype did not, (clone B). Experiments with clone C revealed the following: (a) Production of a translocatable floral stimulus occurred in long days and continuous light. (b) Production of either translocatable inhibitory or promotive factors did not occur in short days. Although flowering was caused by long days, flowering eventually stopped. Experiments designed to test the hypothesis that this was caused by the build up of translocatable inhibitors were inconclusive. There was no evidence in the same experiments that translocatable products produced in short days stopped the cessation of flowering. The effect of the short day light intensity on flowering in long days was also examined. Results indicated that in long day conditions when the photoperiod was near the critical daylength, the light intensity of the short day pretreatment limited flowering. At higher daylengths and in higher long day light intensities, the short day light intensity had no influence on flowering. This supports the idea of Thomas (1981), that a balance between two factors, one inhibitory one promotive controls flowering. Further support for this concept came from studies with clone B in which it was found that a cool pretreatment would enable clone B to flower in continuous light but not in 16h photoperiods. Other experiments with clone B, showed that it produced a translocatable floral stimulus in continuous light. There was no evidence that clone B produced translocatable inhibitors in vegetative conditions although there were indication that warm conditions could inhibit the response of the apex to the floral stimulus. Grafts of clone C on clone C, clone B on clone C, Kalinin A on clone C, were used to test the hypothesis that apical factors limited apical responses to the floral stimulus. Given that clone B had the weakest response to the floral stimulus from clone c, and Kalinin A had a stronger response than clone C it would seem that the hypothesis is correct. Grafts were also used to test the hypotheses that (a) Clone B produced translocatable inhibitors which blocked flowering. (b) Clone B produced a translocatable floral stimulus which it was inhibited from responding to. Neither hypothesis was supported by the results. In conclusion it appeared that a balance between two factors controlled the amount of the floral stimulus translocated from the leaves. It also seemed likely that a interaction between the floral stimulus and the apex had a regulatory role. Differences between white clover genotypes are probably due to differences in apical and leaf processes. The limitations of the experimental methods and futive experiments were also discussed.
Keywords: Inflorescences; White clover